Reduced Cytosolic Calcium as an Early Decisive Cellular State in Parkinson’s Disease and Synucleinopathies - Betzer, Cristine; Jensen, Poul Henning (Frontiers in Neuroscience, 2018)
The more than 30-year-old Calcium hypothesis postulates that dysregulation in calcium dependent processes in the aging brain contributes to its increased vulnerability and this concept has been extended to Alzheimer’s disease and Parkinson’s disease. Central to the hypothesis is that increased levels of intracellular calcium develop and contributes to neuronal demise. We have studied the impact on cells encountering a gradual build-up of aggregated alpha-synuclein, which is a central process to Parkinson’s disease and other synucleinopathies. Surprisingly, we observed a yet unrecognized phase characterized by a reduced cytosolic calcium in cellular and neuronal models of Parkinson’s disease, caused by α-synuclein aggregates activating the endoplasmic calcium ATPase, SERCA. Counteracting the initial phase with low calcium rescues the subsequent degenerative phase with increased calcium and cell death – and demonstrates this early phase initiates decisive degenerative signals. In this review, we discuss our findings in relation to literature on calcium dysregulation in Parkinson’s disease and dementia.